Spatial Analysis of Agricultural Eco-Efficiency and High-Quality Development in China - Wang, Guofeng; Mi, Lingchen; Hu, Jinmiao; Qian, Ziyu (Frontiers in Environmental Science, 2022)
High-quality development has become a new requirement for China's social and economic development. As the important industry related to the national economy and people's livelihood, achieving high-quality development in agriculture has become the most urgent task currently facing agriculture. Based on agricultural input-output data from 2001 to 2019 and the SBM-Undesired model, this paper focuses on Agricultural Eco-efficiency, a key indicator related to the high-quality development of agriculture, to measure the temporal and spatial evolution of Agricultural Eco-efficiency. The results show that the Agricultural Eco-efficiency has increased from 0.363 in 2001 to 0.818 in 2019, with a growth rate of 125.34%, and the provinces with higher Agricultural Eco-efficiency are mainly located in the Eastern regions. In addition, there is a U-shaped change trend between the Agricultural Eco-efficiency and the total output value of agriculture, forestry, animal husbandry and fisher. In other words, the provinces with the total output value of agriculture, forestry, animal husbandry and fishery in the low range and high range enjoy higher Agricultural Eco-efficiency. Compared with the Eastern region, the Middle of Yellow River and Middle of Yangtze River have great potential to reduce carbon emissions. In order to achieve high-quality agricultural development, it is necessary to pay attention to key indicators for improving Agricultural Eco-efficiency, and the technology development of the Central and Western will be very useful to decrease the gap.